The body of the liberation guerrilla war veteran - Mlambo, Obert; Gwekwerere, Tavengwa (AAeO - Afrikanistik-Aegyptologie-Online, 2021)
Since the advent of Zimbabwe’s independence in 1980, bodies of veterans of the national liberation war have featured prominently in the southern African country’s politics, mainly at the service of the ruling Zimbabwe African National Union-Patriotic Front (ZANU-PF). This article explores the continuum of activities in which veterans’ bodies functioned as instruments which ZANU-PF relied upon in consolidating power in post-2000 Zimbabwe. It trains its lens on the agency of liberation war military veterans in the unfolding of the Fast Track Land Reform Programme (FTLRP), state funerals at National Heroes Acre and provincial heroes acres scattered across Zimbabwe, presidential send-offs and welcomes at Harare International Airport, marches in solidarity with ruling elites, and at ZANU-PF political rallies. In these spaces, bodies of war veterans functioned as vectors of partisan political views, purveyors of state-centric versions of the nation’s history, embodiments of an ideology of war and exemplars of state-sanctioned versions of patriotism. Operating in a context framed by the rise of vibrant political opposition to ZANU-PF’s political hegemony in the form of the Movement for Democratic Change (MDC), war veterans in post-2000 Zimbabwean politics served largely to contain forces that threatened the erstwhile revolutionary party’s power retention interests.